The Effect of Providing Structured Work Training Programmes and Satisfactory Compensation on Employee Performance in The Production Division - Nurhidayat, Fajar; Jazuli, A. Muhamad (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of job training and compensation on the performance of production division employees in order to identify managerial strategies for improving employee performance.   Design/Methodology/Approach – This study employs a quantitative explanatory research design to examine the causal relationships among the variables. The population consisted of 70 production division employees, all of whom were included as respondents using a saturated sampling technique. Data were analyzed using multiple linear regression supported by validity, reliability, classical assumption, and hypothesis tests with SPSS version 25.   Findings –  The results indicate that job training has a positive and significant effect on employee performance. Compensation also has a positive and significant effect on employee performance. Furthermore, job training and compensation simultaneously have a positive and significant influence on employee performance. These findings suggest that improving training programs and providing fair compensation are essential strategies for enhancing employee performance and organizational productivity.   Originality/Value This research is original in simultaneously examining the effects of training and compensation within a production-division context using a saturated sampling approach. The findings provide practical value by offering empirical evidence for managers to optimize human resource strategies to enhance employee performance.